Maternal race and neonatal outcomes after elective repeat cesarean delivery. (March 2014) - Vilchez, Gustavo; Chelliah, Anushka; Argoti, Pedro; Jeelani, Roohi; Bahado-Singh, Ray
Abstract Objective: To determine the effect of race in the risks of prematurity-related complications (PRC) after elective repeat cesarean delivery (ERCD). Methods: The NCHS-CDC Database for the U.S. (2004–2008) was used. ERCD cases were included. Exclusion criteria were multiple gestation, trial of labor, fetal anomalies, history of diabetes and/or hypertension. PRC analyzed were: Apgar score, assisted ventilation, intensive care admission, surfactant use, antibiotic use, seizures. Regression analysis was performed to calculate the odds ratio (OR) of these variables. Deliveries at 36–40 weeks were studied with 40 weeks as reference. Results: Totally, 785 340 ERCDs were performed between 36 and 40 weeks. For the overall population, there was not difference in adverse outcomes between 39 and 40 weeks. The rates of PRC were significantly higher in newborns at 38 compared to 39 weeks, with similar findings in sub-analysis of whites. For African-Americans, the rate of PRC was not significantly different at 38 compared to 39 weeks. Conclusions: We report increased rates of PRC after ERCD before 39 weeks, similar findings from smaller hospital-based studies. For African-American newborns, there was no further decrease in PRC after 38 weeks suggesting earlier maturation of these fetuses. The study does not propose changing the current 39 weeks threshold for ERCD.